The Implementation of the Flipped Classroom Learning Method to Address Conceptual Understanding on Dynamics Concepts - Hendrawan, Wawan; Haryadi, Rudi; Atikah, Cucu (International Journal of STEM Education for Sustainability, 2025)
The purpose of this study was to determine how well students understood dynamics principles when using the flipped classroom learning methodology. A pretest-posttest control group was included in the quasi-experimental design of the study. A total of 72 students were separated into two groups, namely the experimental group using the flipped classroom model and the control group with the conventional method. Questionnaires to gauge student impressions and two-tier multiple-choice examinations to gauge conceptual knowledge were the primary tools. According to the research findings, the experimental group's normalized gain value of 0.67 (high category) significantly outperformed the control group's 0.41 (medium category) in terms of conceptual comprehension. The two groups differed significantly (p 0.05) according to the independent t-test. These findings support the effectiveness of the flipped classroom in enhancing conceptual understanding, encouraging active student engagement, and aligning with the principles of the Merdeka Curriculum. However, the success of implementing this model is also influenced by the readiness of teachers, students, and adequate technological infrastructure. For other areas of physics, similar models should be developed, and further mixed-methods research is needed to further explore students' experiences.